Analisis Kebutuhan Media Pembelajaran Berbasis Web Google-Sites Materi Statistika Pada Pembelajaran Matematika SMA - Gumilar, Cecep Bermana Sakti; Effendi, Kiki Nia Sania (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2022)
This research was conducted to analyze the need for learning media that can support face-to-face and distance learning with web-based google sites on statistical material in high school mathematics learning. The research subjects were 19 students of class XII in Karawang Regency. This research is a descriptive qualitative research that refers to the analysis of Miles and Huberman. The results of this study are (1) student having a low interest in learning mathematics in statistical material, (2) the use of learning media can affect the learning process, (3) learning media that are less attractive so that students find mathematics difficult, (4) media that are in accordance with what is expected. What the teacher wants is the Google sites web-based learning media. So the researchers concluded that the development of web-based learning media for Google sites on statistical material was needed to facilitate students and teachers in learning mathematics for class XII senior high school.Keywords: Google Sites; Requirements; Electronic Media; Statistics.